Maxima on the Electrical Conductivity Isotherms in Aqueous Solutions of Some Transition Metal Salts - almismary, Saber El–Sayed Mansour; Haroon, Mohammed Hasan (Al-Mukhtar Journal of Sciences, 1999)
The electrical conductivity, viscosity, and pH of aqueous solutions of some transition metal salts have been measured over a wide concentration range at 25°C. It has been found that curves of specific conductance versus concentration passes through maxima. There is a wealth of experimental evidence for the existence of a relation between the concentration at the electrical conductivity maximum and hydration, charge, and degree of association of solvates in solution. An increase in hydration leads to a decrease in the concentration at the maximum. Electrolytes having the same charge have a maximum in the same concentration range. An analysis of the results that have been obtained suggests that in the concentration range corresponding to the electrical conductivity maximum there is a change in the structure of the solution from water–like to the structure of a liquid electrolyte.